2012
DOI: 10.5660/wts.2012.1.4.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage and No-tillage of Winter Green Manure Crops on Yield of Red Pepper in Plastic Film House

Abstract: To determine the effect of winter green manure crops for tillage and no-tillage organic pepper cultivation in plastic film house, five different green manure crops were cultivated during winter season. In nutrition composition of green manure crops, total nitrogen contents were higher in Vicia hirsuta and Vicia angustifolia than any other crops. The average dry weights of green manure crops were 8.3 ton per ha in tillage and 7.0 ton per ha in no-tillage, among green manure crops that of Secale cereale was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Previous studies have shown that crop yield under no‐till culture is somewhat lower than that under conventional culture in Korea. Won et al () grew a green manure crop during winter, harvested it in the next spring and then transplanted seedlings of a red pepper variety under CT and NT conditions; they found that the red pepper yield was lower in the NT treatment than in the CT treatment. A similar study with a corn variety for ethanol production under CT and NT treatments with a hairy vetch cultivation as a surface cover crop revealed that the corn yield in the NT treatment was between 58.9 and 89.8% of that in the CT treatment (Kim et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that crop yield under no‐till culture is somewhat lower than that under conventional culture in Korea. Won et al () grew a green manure crop during winter, harvested it in the next spring and then transplanted seedlings of a red pepper variety under CT and NT conditions; they found that the red pepper yield was lower in the NT treatment than in the CT treatment. A similar study with a corn variety for ethanol production under CT and NT treatments with a hairy vetch cultivation as a surface cover crop revealed that the corn yield in the NT treatment was between 58.9 and 89.8% of that in the CT treatment (Kim et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the results from these studies were important, they were not suitable for describing the characteristics of NPS pollution generation and discharge nor for developing proper best management practices (BMPs) from the fields where intensive farming is practiced. Some studies related to tillage methods have been conducted (Kim et al , ; Won et al , ). But the focus of these studies has been about crop growth and productivity; the environmental aspects of different management practices have not been well explored as yet.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical properties of the soil before sowing hairy vetch and rye. (Won et al, 2012;Lim et al, 2012), (Fageria et al, 2005), 1% (Lee et al, 2006;Kim et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…풋거름작물에는 호밀(Secale cereal L.)과 수단그라스(Sorghum biocolor L.) 등 화본과와 헤어리베치(Vicia villosa Roth)와 크로탈라리아(Crotalaria juncea L.) 등 두과작물로 분류할 수 있다. 호밀과 수단그라스는 작물 재배기간 동안 두과작물과 비교 하여 높은 생체중을 얻을 수 있어 (Won et al, 2012;Lim et al, 2012), 토양환원을 통해서 유기물 함량을 높이고 용적밀도를 낮 추는 효과는 있지만 (Fageria et al, 2005), 공중질소를 고정하는 능력이 없고 식물체의 질소함량이 적기 때문에 후작물 채소에 대한 질소공급능력이 낮다 (Lee et al, 2006).…”
Section: 서 언unclassified